Michael Addition-initiated Sequential Reactions from 1,3-dicarbonyls for the Synthesis of Polycyclic Heterocycles - Bugaut, Xavier; Bonne, Damien; Coquerel, Yoann; Rodriguez, Jean; Constantieux, Thierry (Current Organic Chemistry, 2013)
This review aims to highlight the most significant recent developments on synthetic strategies involving consecutive, domino and multicomponent reactions featuring a Michael addition-initiating step for the synthesis of polycyclic heterocycles from 1,3- dicarbonyls. These original sequences constitute more efficient and eco-compatible alternatives to known synthetic approaches to heterocyclic compounds allowing for an even faster and highly desirable generation of molecular diversity and complexity.
Keywords: Polycyclic heterocycles